Level of Computational ThinkingLevel of Computational Thinking Skills among Secondary Science Student: Variation across Gender and Mathematics Achievement Skills among Secondary Science Student: Variation across Gender and Mathematics Achievement - Samri Chongo; Kamisah Osman; Nazrul Anuar Nayan (Science Education International, 2020)
Computational thinking (CT) is often associated with computer science and mathematics in general. However, the involvement of computer science according to gender is seen to be imbalanced. Therefore, this study aimed to identify the level of students’ CT skills by gender and their relationship to achievement in mathematics. The study employed survey research design and purposive sampling that involved 128 participants from four science stream students in one of the states in Malaysia (n = 128). The measurement of CT skills was done using a modified CT test adapted from the previous studies. The results of the study were analyzed using descriptive and inferential statistics. Spearman correlational analysis was applied to examine the relationship between CT skill and mathematical achievement and students’ t-test analysis was used to determine the difference in CT skills across gender. The study found that the students’ CT skills were at the honors level. The relationship between CT skills and mathematics achievement was statistically significant, whereas there exist no significant gender differences in CT skills. This study suggests that the teaching of mathematical logic needs to be considered to improve students’ CT skills.